High-performance ammonia fixation electrocatalyzed by ReS2 nanosheet array. (22nd June 2021) - Zhang, Lunwen; Xue, Xiaodong; Gao, Min; Zhao, Jinxiu; Yan, Tao; Yu, Cuiping; Zhao, Lei; Ren, Xiang; Wei, Qin
Abstract : The industrial-scale NH3 production still heavily depends on the Haber–Bosch process, which not only demands high energy consumption but also emits a large amount of CO2 . Abstract : The industrial-scale NH3 production still heavily depends on the Haber–Bosch process, which not only demands high energy consumption but also emits a large amount of CO2 . The electrochemical fixation of N2 to NH3 under ambient conditions is regarded as an eco-friendly and sustainable approach, but stable and efficient electrocatalysts are demanded for the N2 reduction reaction under ambient conditions. In this communication, ReS2 nanosheet array on carbon cloth (ReS2 /CC) is first utilized in NRR. This ReS2 /CC exhibits high catalytic activity and strong long-term electrochemical durability. The Faraday efficiency of ReS2 /CC is 0.78% and the NH3 yield of ReS2 /CC is 3.61 × 10 −10 mol s −1 cm −2 at −0.4 V versus reversible hydrogen electrode in 0.1 M HCl.